Active Social Media Users on Conspiracy Facebook Groups. Political, Leadership, and Worldview Profiles - Agnieszka Turska-Kawa; Irena Pilch (Communication Today, 2025)
Social media outlets seem a natural place for spreading conspiracy theories. Facebook groups addressed to supporters of conspiracy theories are an essential element of these spaces. The presented research was conducted using a semi-structured interview method among the most active members of groups on Facebook focusing on themes promoting conspiracy thinking. Considering different motivations for activity on social media, we divided the sample into three subgroups, taking into account the degree of conspiratorial ideation. The study aimed to create profiles of characteristics for the “convinced” group (declaring a strong belief in conspiracy theories) and the “seeking” group (declaring less certainty in this regard). Subsequently, the differences between those belonging to the groups in terms of the three highlighted areas of functioning were analysed. Our study showed that worldview characteristics differentiated the groups with different levels of conspiracist ideation more clearly than psychological or political characteristics.